2019
DOI: 10.1002/ejlt.201800376
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Resources from Insects: Exploitation, Properties, and Refining of Fat Obtained by Cold‐Pressing from Hermetia illucens (Black Soldier Fly) Larvae

Abstract: Hermetia illucens (black soldier fly) larvae are dried and mechanically treated by an oil seed screw press to extract the fat. This leads to an accumulation of the protein in the press cake with a protein content of 42% dry base. The amino acid composition fulfills the scoring patterns of FAO/WHO for adults. The extracted fat fraction has an interesting fatty acid composition with lauric acid (48%), myristic acid (11%), and palmitic acid (16%) as predominant representatives, very similar to palm kernel fat and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 37 publications
6
31
2
1
Order By: Relevance
“…The MCFAs composition of HIL oil is very similar and can replace palm kernel or coconut oil, as additives and even pharmaceuticals (Matthäus et al, 2019;Rabani et al, 2019). Both vegetable oils are products of plants from tropical climates, where they are abundant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MCFAs composition of HIL oil is very similar and can replace palm kernel or coconut oil, as additives and even pharmaceuticals (Matthäus et al, 2019;Rabani et al, 2019). Both vegetable oils are products of plants from tropical climates, where they are abundant.…”
Section: Discussionmentioning
confidence: 99%
“…The impact on the environment is also considerable, as an increase in demand for vegetable oils and biofuels contributes to water waste, tropical deforestation, loss in biodiversity, and habitat fragmentation. For this reason, palm kernel and coconut oil are currently criticized from an ecological point of view (Wang and Shelomi, 2017;Matthäus et al, 2019;Verheyen et al, 2020;Kierończyk et al, 2020). Therefore, in a vision of the circular economy, it would be possible to manage, reduce, and efficiently use organic waste for HIL rearing as a sustainable source of nutrients (according to the 4R of the EU Parliament Directive no.…”
Section: Discussionmentioning
confidence: 99%
“…Cold-pressed BSFL oil exhibited higher oxidative stability (50.5 h), which is comparable to coconut (30-250 h) and palm kernel oil (15-100 h), and this can be attributed to the higher amount of saturated fatty acids present in the oil and possibly the high content of ∆5-avenasterol present [44]. Consumers' perception of insect fat (BSFL) as a partial butter replacement for certain bakery products (cake, cookie and waffle) was explored, and the results showed that BSFL fat could replace 25% of the butter in the products studied without changing the overall food experience and liking for the participants.…”
Section: Lipids In Human Nutritionmentioning
confidence: 93%
“…Nevertheless, both the studies discovered that there was a limitation in the extent to which the BSFL can retain these diet-derived fatty acids and witnessed a decrease in the oil yield when drastic diet changes were adopted. The BSFL oil is dominated by saturated triacylglycerides (TAG) with LaLaLa accounting for 27.6% of total TAGs, followed by LaLaM with 16% and LaMM with 15.1%, respectively [44]. Fish waste (discarded round sardinella) as a substrate was used to augment the EPA, DHA and total polyunsaturated fatty acids (PUFAs) content in the lipid fraction of BSFL.…”
Section: Lipidsmentioning
confidence: 99%
“…Для минимизации стадии нагрева для дальнейшей обработки средняя температура биомассы была установлена в качестве второго критерия с использованием ранее полученных данных [10]. Последующий отбор критериев проводился в соответствии с работами [14][15][16], а также для получения наибольшего положительного эффекта на процесс сушки.…”
Section: рисунок 1 -образцы биомассы в контейнерах для сушки Figure 1unclassified